Investigation of the relationship between basal metabolic rate and body composition in young adults using CHAID analysis - Yildirim, Irfan; Dogan, Ilkay; Isik, Ozkan; Yildirim, Yunus; Karagoz, Seniz (Progress in Nutrition, 2020)
Study Objectives: Basal metabolic rate (BMR) is the most important component of the individual’s daily energy-consuming. Personal and environmental factors make a difference in BMR. Body composition is the most important variable for BMR, from these factors. In this context, the aim of this study was to examine the relationship between BMR and body components in young adults and to determine the most effective body component on BMR. Methods: The sample of this study consisted of 229 women and 123 men, a total of 349 young adult individuals. All measurements of the participants were carried out in the physiology laboratory of the School of Physical Education and Sports, Afyon Kocatepe University. Participants’ height measurements were measured using Seca 213 (Germany) 1 mm precision portable stadiometer, body compositions (Body weight, Fat Mass, Free-Fat Mass, and Total Body Water) and BMR using a bioelectrical impedance analyzer. In the analysis of the obtained data, CHAID analysis was applied using the SPSS package program to explain the relationship between basal metabolic rate and body composition as well as descriptive statistics. Results: It was determined that the BMR of men and women differed statistically. It was determined that the most important body component affecting BMR in young adult women and men is free-fat mass. Conclusion: The BMR was predicted by 83.91% in young adult women and 70.39% in men by free-fat mass. Moreover, it was determined that BMR increased as the free-fat mass increased.